Toxicity and Apoptosis Test of 96% Ethanol Extract of Agelas Cavernosa on Vero Cells - Mahbub, Khafid; Rusmalina, Siska; Indriono, Anik; Mahfur, Mahfur; Julian, Rixzal Azis; Maulidya, Dina Achada; Dika, Ika Vina; Rohmaniah, Salis Alyatur (Jurnal Biologi Tropis, 2025)
Agelas cavernosa sponge is a sponge from the Demospongiae class which includes 90% of all types of sponges. Agelas cavernosa sponge is known to have antibacterial activity. Research data on the toxicity and apoptosis test of Agelas cavernosa sponge on vero cells as far as researchers know has not been tested. The purpose of this study was to determine the toxicity and apoptosis of Agelas cavernosa ethanol extract. The research method was carried out using the MTT Assay method for toxicity testing and the flowsitometry method for apoptosis testing. Alkaloids, flavonoids, saponins, terpenoids, and polyphenols were all detected in the Agelas cavernosa ethanol extract, according to the results of phytochemical screening. The apoptosis test yielded vero cell viability of 82.2%, whereas the toxicity test yielded an LC50 value for vero cells of 197.84 ppm.